(untitled) (Docentes 2.0 Journal, 2018)
The term gamification refers to the adoption of mechanics, instructions and components of the games, for any organizational context in which specific motivations or behaviors are required. The general objective of this research was to determine the conceptual framework that points out the phenomenon of gamification as a useful alternative for supporting learning processes in the context of educational sciences, supporting the picture of opportunities offered by current information technologies and Communication, Learning and Knowledge Technologies, in conjunction with the Technologies for Empowerment and Participation, which characterize the demands of modern knowledge technologies. This is a job in which you can see a focus on the game processes and the benefit that leads to their involvement inside and outside the classroom. The methodology applied was documentary-bibliographic, where the analyzes contributed by some authors such as Dale (1946), Kapp (2012), Marín & Hierro (2013), (Deterding et al., 2011), Moll (2014) were condensed. , (Contreras and Eguia, 2016), PUCV (2017), Prensky (2001); who served as a reference base for the configuration of the arguments in the educational subject, added to the innumerable technological utilities that can be adapted to the curriculum and to the operation according to the strategies in the formal instruction systems.